The Intriguing History of Cancer Immunotherapy - Dobosz, Paula; Dzieciątkowski, Tomasz (Frontiers in Immunology, 2019)
Immunotherapy is often perceived as a relatively recent advance. In reality, however, one should be looking for the beginnings of cancer immunotherapy under different names as far as in the Antiquity. The first scientific attempts to modulate patients’ immune systems to cure cancer can be attributed to two German physicians, Fehleisen and Busch, who independently noticed significant tumour regression after erysipelas infection. The next significant advances came from William Bradley Coley who is known today as the Father of Immunotherapy. It was Coley who first attempted to harness the immune system for treating bone cancer in 1891. His achievements were largely unnoticed for over fifty years, and several seminal discoveries in the field of Immunology, such as the existence of T cells and their crucial role in immunity in 1967, stepped up the research towards cancer immunotherapy known today. The following paper tracks cancer immunotherapy from its known beginnings up until recent events, including the 2018 Nobel Prize award to James Allison and Tasuku Honjo for their meticulous work on checkpoint molecules as potential therapeutic targets. That work has led to the successful development of new checkpoint inhibitors, CAR T-cells and oncolytic viruses and the pace of such advances brings the highest hope for the future of cancer treatment.